2018
DOI: 10.1111/jocn.14273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loneliness on illness perception in persons with a chronic disease

Abstract: The knowledge of clinical nurses about perception of patients with chronic illnesses and conditions affecting that perception will enhance compliance with the illness management or treatment strategies. Clinical nurses should observe residents closely for signs of depression and loneliness and support their sense of coherence to reduce emotional and social loneliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Loneliness may impact people with chronic illness in different ways. Apart from the physiological consequences mentioned above, perceptions of loneliness can adversely impact general wellbeing (6,7), coping (8), medication management (9,10), and perception of illness and pain (11)(12)(13). In the literature, loneliness is defined in different ways and within different theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness may impact people with chronic illness in different ways. Apart from the physiological consequences mentioned above, perceptions of loneliness can adversely impact general wellbeing (6,7), coping (8), medication management (9,10), and perception of illness and pain (11)(12)(13). In the literature, loneliness is defined in different ways and within different theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness may impact people with chronic illness in different ways. Apart from the physiological consequences mentioned above, perceptions of loneliness can adversely impact general well‐being (Ernst & Cacioppo, 1999; Miller, 1985), coping (Lopez‐Martinez, Esteve‐Zarazaga, & Ramirez‐Maestre, 2008), medication management (DiMatteo, 2004; Kusaslan Avci, 2018), and perception of illness and pain (Jaremka et al, 2013; Ozkan Tuncay, Fertelli, & Mollaoglu, 2018; Smith, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of loneliness may have a negative impact on diabetic outcomes, while the long‐term and demanding treatment of the disease itself and its potential complications may affect patient's perception of treatment and increase the feeling of loneliness. Studies conducted in a group of patients with chronic diseases showed that the participants perceived their loneliness level as moderate and that their illness perception was negatively affected as their loneliness levels increased (Özkan Tuncay et al., 2018). Loneliness has an impact on self‐management ability in chronically ill individuals (Theeke et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the social components of activity are important in keeping older adults motivated and engaged, with social isolation and loneliness known to reduce engagement in both the community and PA [ 26 , 27 ]. Social isolation is defined as an ‘objective lack of relationships and social interaction ’ and loneliness as ‘ a subjective and distressing feeling [ 28 ].’Older adults have an increased risk of social isolation and loneliness stemming from events such as transitioning into retirement [ 29 ].…”
Section: Introductionmentioning
confidence: 99%